Capacity building for participatory irrigation management in Sindh Province of Pakistan - Memon, Yameen; Talpur, Mustafa; Murray-Rust, Hammond (International Water Management Institute, 2001)
Based on a project in which IWMI assessed the training needs of the farmers under the Farmer Managed Irrigated Agriculture (FMIA), the study highlights the importance of training in areas such as; effective communication strategies and conflict resolution, equitable water distribution, optimum use of water, financial management and developing a business plan.